1998
DOI: 10.1111/j.1445-2197.1998.tb04724.x
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer Following Colectomy and Ileorectal Anastomosis for Familial Adenomatous Polyposis

Abstract: Background: Familial adenomatous polyposis (FAP) has historically been treated by colectomy and ileorectal anastomosis (IRA). Preservation of the rectum allows the subsequent development of cancer in the rectum. The risk of rectal cancer following ileorectal anastomosis in the Australian population has not been published to date. Methods: An audit of the Familial Adenomatous Polyposis Registry of Western Australia was undertaken to assess patients who had undergone colectomy and ileorectal anastomosis. Fifty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The localization of the Stk11 gene within this region is of particular interest in view of the causative role of this serine/threonine kinase in Peutz-Jeghers syndrome, an inherited susceptibility to intestinal cancer characterized by multiple hamartomatous polyps throughout the upper GI tract and a high risk of developing cancer in the intestine and other organs. 53 To further restrict the size of the chromosomal intervals affected by gain/loss events and pinpoint specific conserved genes that play rate-limiting roles in intestinal adenoma formation in the mouse and human, we compared array CGH profiles from early FAP adenomas (obtained from carriers of known APC germline mutations) and from histology-matched intestinal tumors from Apc ϩ/1638N mice. The results of this comparative analysis (Table 2) have indicated the presence of a surprisingly high number of chromosomal aberrations shared between mouse upper GI and human colorectal adenomas, notwithstanding the different anatomical location of these two groups of GI tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of the Stk11 gene within this region is of particular interest in view of the causative role of this serine/threonine kinase in Peutz-Jeghers syndrome, an inherited susceptibility to intestinal cancer characterized by multiple hamartomatous polyps throughout the upper GI tract and a high risk of developing cancer in the intestine and other organs. 53 To further restrict the size of the chromosomal intervals affected by gain/loss events and pinpoint specific conserved genes that play rate-limiting roles in intestinal adenoma formation in the mouse and human, we compared array CGH profiles from early FAP adenomas (obtained from carriers of known APC germline mutations) and from histology-matched intestinal tumors from Apc ϩ/1638N mice. The results of this comparative analysis (Table 2) have indicated the presence of a surprisingly high number of chromosomal aberrations shared between mouse upper GI and human colorectal adenomas, notwithstanding the different anatomical location of these two groups of GI tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with extensive rectal involvement usually undergo total proctocolectomy with ileal-pouch anal anastomosis (IPAA) [ 3 ]. Many such patients develop progressive polyposis in the retained rectum [ 6 , 7 ] or ileal pouch [ 8 10 ]. Despite excision of the main at-risk organ(s), many patients develop duodenal adenomas and require frequent surveillance and endoscopic or surgical intervention [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jenner et al . 21 only included patients with a confirmed mutation. Five studies reported a cumulative incidence of rectal cancer ranging from 3% 22 to 17.2% 19 at 5 years, 7.7% 23 to 24.1% 19 at 10 years, 11% 22 to 23% 23 at 20 years, and 24% 22 at 30 years after the primary IRA.…”
Section: Resultsmentioning
confidence: 99%